MiR-146b-5p Plays a Critical Role in the Regulation of Autophagy in ∆per Brucella melitensis-Infected RAW264.7 Cells. (20th January 2020) - Hanwei, Jiao; Nie, Xin; Zhu, Huapei; Li, Baobao; Pang, Feng; Yang, Xiaohong; Cao, Ruiyong; Yang, Xiaojian; Zhu, Shu; Peng, Dongmei; Li, Yaying; Li, Guohua; et al.
Abstract : Brucella -caused brucellosis is one of the most widespread worldwide zoonoses. Lipopolysaccharide (LPS) of Brucella, which functions as pathogen-associated molecular patterns (PAMPs), is an important virulence factor that elicits protective antibodies. Per of B . melitensis is involved in the biosynthesis of the O-side chain of LPS. Autophagy is a crucial element of the innate immune response against intracellular pathogens including Brucella . In this study, we observed that autophagy was inhibited in RAW264.7 cells infected with Brucella melitensis ∆per. And, a high-throughput array-based screen and qRT-PCR validation were performed to identify the differentially expressed miRNAs in RAW264.7 cells infected with B. melitensis M5-90 ∆per. The results suggested that mmu-miR-146a-5p, mmu-miR-155-5p, mmu-miR-146b-5p, and mmu-miR-3473a were upregulated and mmu-miR-30c-5p was downregulated. During B. melitensis M5-90 ∆per infection, the increased expression of miR-146b-5p inhibited the autophagy activation in RAW264.7 cells. Using a bioinformatics approach, Tbc1d14 was predicted to be a potential target of miR-146b-5p . The results of a luciferase reporter assay indicated that miR-146b-5p directly targeted the 3′-UTR of Tbc1d14, and the interaction between miR-146b-5p and the 3′-UTR of Tbc1d14 was sequence-specific. High-throughput RNA-Seq-based screening was performed to identify differentially expressed genes in Tbc1d14-expressing RAW264.7 cells, and these were validated by qRT-PCR. Among the differentially expressed genes, four autophagy associated genes, IFNγ-inducible p47 GTPase 1 ( IIGP1 ), nuclear receptor binding protein 2 ( Nrbp2 ), transformation related protein 53 inducible nuclear protein 1 ( Trp53inp1 ), and immunity-related GTPase family M member 1 ( Irgm1 ), were obtained. Our findings provide important insights into the functional mechanism of LPS of B. melitensis .